2019
DOI: 10.5152/tjar.2019.20856
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of Vocal Cord-Carina Distance and Tracheal Length in the Indian Population

Abstract: the manuscript, references should be cited using Arabic numbers in parentheses. The reference styles for different types of publications are presented in the following examples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 16 publications
0
8
2
1
Order By: Relevance
“…VKM'nin doğru bir şekilde ölçülebilmesi için entübasyon sırasında vokal kordların net olarak görülmesi (Cormack-Lehane I-II) ve ET üzerinde bulunan işaret noktasının tam olarak vokal kordlarda bırakılması gerekmektedir. Biz de çalışmamızda, diğer çalışmalardan [13] farklı olarak Cormack-Lehane 3 ve 4 olan hastaları da çalışmamıza dâhil edebilmek amacıyla video laringoskopun zor entübasyon bleydi kullanılarak tüp üzerinde bulunan işaret çizgilerini tam olarak vokal kordlar üzerinde bırakmasını sağladık.…”
Section: Discussionunclassified
“…VKM'nin doğru bir şekilde ölçülebilmesi için entübasyon sırasında vokal kordların net olarak görülmesi (Cormack-Lehane I-II) ve ET üzerinde bulunan işaret noktasının tam olarak vokal kordlarda bırakılması gerekmektedir. Biz de çalışmamızda, diğer çalışmalardan [13] farklı olarak Cormack-Lehane 3 ve 4 olan hastaları da çalışmamıza dâhil edebilmek amacıyla video laringoskopun zor entübasyon bleydi kullanılarak tüp üzerinde bulunan işaret çizgilerini tam olarak vokal kordlar üzerinde bırakmasını sağladık.…”
Section: Discussionunclassified
“…Measurements using FOB and airway USG were performed as described in the previous literature. [ 10 11 ]…”
Section: Methodsmentioning
confidence: 99%
“…In Indian adults, the reported average cricoid-to-carina distance (D CrC ) is 9.7–11.2 cm in males and 9.4–10.4 cm in females. [ 9 10 ] Hence, while securing the ETT by the IGM technique, placing fixed length (≈ 9 cm) of commercially available tubes beyond the vocal cords could lead to suboptimal placement. [ 9 ] However, placing the proximal cuff just beyond the cricoid-cartilage is likely to provide optimal ETT placement as only around 6–7 cm segment of the ETT (between proximal end of cuff to tube tip) lies beyond the cricoid.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been proposed to determine the appropriate ET placement. Methods for determining the appropriate depth of ET include age, height, ET internal diameter (ID)-based formulas, chest X-ray-based methods, and fiberoptic bronchoscopy 9 , 10 . Previous studies have shown that these methods have limitations in clinical practice due to the lack of accuracy of formula-based methods and the inconvenience of using the equipment.…”
Section: Introductionmentioning
confidence: 99%